Fear : Trump in the White House - Woodward, Bob, 1943- (New York, NY : Simon & Schuster Paperbacks, 2019)
Investigative reporter Bob Woodward describes life inside President Donald Trump's White House and precisely how he makes decisions on major foreign and domestic policies. Woodward draws from hundreds of hours of interviews with firsthand sources, meeting notes, personal diaries, files and documents. The focus is on the explosive debates and the decision-making in the Oval Office, the Situation Room, Air Force One and the White House residence.
Includes bibliographical references and index.
Keywords: Trump, Donald, -- 1946-; Trump, Donald, -- 1946-; Since 2000; Presidents -- United States; Presidents -- United States -- Biography; Politics and government; Presidents; United States -- Politics and government -- 21st century; United States -- Politics and government -- 2017-; United States; Biographies; Biographies